Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

For each $n\in\mathbb{N}$ and $x\in\mathbb{R}$ define $$ g_n(x)=2nxe^{-nx^2}\qquad h_n(x)=g_{n+1}(x)-g_n(x) $$ Prove that $$ \int\limits_0^\infty\sum_{n=0}^\infty h_n(t)dt \neq \sum_{n=0}^\infty\int_0^\infty h_n(t)dt $$ So far, I've shown that the LHS is equal to $0$ by noting that $$ \sum\limits_{n=0}^\infty h_n(t)=g_\infty (t) - g_0(t) = \lim_{n\to \infty} 2nxe^{-nx^2} =0 $$ by L'Hopital's rule. Thus, we have an integral of a constant function equal to $0$, which is $0$.

For the RHS, I've got the integral down to $$ \int\limits_0^\infty h_n(t)dt= \int\limits_0^\infty 2(n+1)xe^{-(n+1)x^2}dx - \int\limits_0^\infty 2nxe^{-nx^2}dx=[e^{-nx^2}-e^{-(n+1)x^2}]_0^\infty=0 $$

This gets me to believe that RHS equals LHS, which is directly contrary to the question. Am I missing something?

share|cite|improve this question

$h_0(t)=2 x e^{-t^2}$ and $\int_0^\infty 2x e^{-t^2} dt=1$. Your argument for $\int_0^\infty h_n(t)dt$ applies just fine to the rest of the $n$, so you end up with $0=1$.

share|cite|improve this answer
Ahh, that makes sense. Thanks heaps. – Lachlan Oct 7 '12 at 14:44

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.